Prevalence of anemia and associated factors among patients with heart failure at Birat Medical College Teaching Hospital - Bista, Madhab; Mehta, Ram Kumar; Parajuli, Surya B.; Shah, Prashant (Nepalese Heart Journal, 2023)
Background and Aims: Anemia is a frequently encountered comorbid illness in heart failure and is associated with poor clinical outcomes. There are limited studies done in Nepal to evaluate its prevalence among patients diagnosed with heart failure. Hence, this study was aimed to find out the prevalence of anemia and associated factors among patients with heart failure at Birat Medical College Teaching Hospital. Methods: A hospital based cross sectional study was conducted from 1st July 2022 to 30 February 2023 among consecutively selected 100 patients at Birat Medical College Teaching Hospital. Socio-demography, clinical features and laboratory parameters to evaluate anemia were obtained. Ethical clearance was taken from the Institutional Review Committee of institute. Collected data was entered in Microsoft Excel and analyzed by Statistical Package for Social Sciences version 23. Frequency, mean, percentage were calculated and chi square test at 0.05% level of significance was used to find the association. Results: The prevalence of anemia was 65%. Out of 100 patients, majority had iron deficiency anemia (40%), followed by anemia of chronic disease (10%). Thirty three percent had iron deficiency without anemia. Female patients 36(75%) and patients with chronic obstructive pulmonary disease (COPD) 15(93.8%) had significantly higher prevalence of anemia (p value <0.05). Conclusions: Nearly two third of heart failure patients had anemia among which iron deficiency anemia was the commonest. Female and patients with COPD had higher prevalence of anemia.